Carmelitas descalzas a ambos lados del Atlántico. La gestión económica de sus conventos - Catalán Martínez, Elena (El Colegio de México, A.C., 2024)
This article contains a comparative analysis of the economic administration of two Discalced Carmelite convents on both sides of the Atlantic, one in Seville and the other in Mexico City. Aside from their foundational chronicles, it also makes use of the accounting books of both institutions. The conclusions are clear: they both developed a great capacity to adapt to their environment in order to guarantee their survival. In the case of Seville, the convent’s chronic debts and the loss of the profitability of its investments were only overcome thanks to an annual rent established by the Duchess of Osuna, making it into a subsidized convent. The Mexican convent had a more positive economic balance, having managed to avoid falling into debt in its initial phase and understanding how to take advantage of the need of Mexican society to increase its social capital through the commercialization of sacred spaces.